Potential Novel Biomarkers Identification in Cervical Cancer Specific to DNA Methylation Using Analytical Pathways - Ranabhat, Bikash; Baral, Madan (International Journal of Applied Sciences and Biotechnology, 2025)
Background: Cervical cancer is a major global health burden, especially in low- and middle-income countries with limited access to screening and treatment. DNA methylation, an epigenetic modification, critically regulates gene expression and cancer progression. This study investigates the relationship between DNA methylation and gene expression in cervical cancer to identify potential biomarkers and therapeutic targets. Objective: To identify potential novel biomarkers in cervical cancer specific to DNA methylation using analytical pathways. Methods: We performed a comprehensive bioinformatics analysis using GEO datasets (GSE122697, GSE63514, GSE46306, GSE168841) and TCGA data. Differentially methylated and expressed genes were identified, followed by functional pathway enrichment, validation, survival analysis, and evaluation of their therapeutic potential. Results: We identified 3 Hypo-HE oncogenes, including PDZK1IP1, TGM3, and S100A7 and 3 Hyper-LE TSGs such as THBS1, TMEFF1, and GREM1, emerged as potential biomarkers for cervical cancer. Conclusion: Our integrative bioinformatics analysis identified six key genes PDZK1IP1, TGM3, S100A7, GREM1, THBS1, and TMEFF1 as promising biomarkers and therapeutic targets in cervical cancer. These genes play critical roles in cancer progression through abnormal methylation and expression patterns. Targeting them may enable more precise, personalized treatment strategies to improve patient outcomes. Int. J. Appl. Sci. Biotechnol. Vol 13(4): 180-192.